Gender roles in collective management of aquatic resources in Bangladesh - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Floodplain wetlands are the major common natural resource in Bangladesh. Their rivers, beels (lakes), baors (oxbow lakes), haors (large deeply flooded depressions), and floodplains support some 260 fish species. Bangladesh wetlands also have over 2,900 local rice varieties, at least 13 species of edible wetland plants, many other plants that are used for fodder, medicine, mat making and fuel wood, shrimps and crabs used as human food, and molluscs that are used as feed for domestic ducks and in prawn culture. Wetland plants also provide natural protection against wave erosion. About 80 percent of rural households catch fish for food or to sell. About 60 percent of animal protein consumption comes from fish, and of this, 80 percent is from freshwater fish. However, fish consumption declined between 1995-96 and 2000 by 14 percent to 11.1 kg/person/year.